2013
DOI: 10.1007/s10661-013-3327-8
|View full text |Cite
|
Sign up to set email alerts
|

Single drop microextraction and gas chromatography–mass spectrometry for the determination of diflufenican, mepanipyrim, fipronil, and pretilachlor in water samples

Abstract: An analytical method for the determination of diflufenican, mepanipyrim, pretilachlor, and fipronil in water samples was developed using single drop microextraction in the direct immersion mode and gas chromatography-mass spectrometry. A factorial fractionated design of type 2(6-1) at two levels was performed, to study the influence of experimental variables such as ionic strength, pH, agitation speed, extraction time, drop volume, and sample volume. To establish the optimal conditions for the variables that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sha‐Sha et al (2013) proposed magnetic solid‐phase extraction (MSPE) comprising graphene nanocomposite (G‐Fe 3 O 4 ) as the adsorbent, coupled with dispersive liquid–liquid microextraction (DLLME) using GC‐FID to detect five chloroacetanilide herbicides including pretilachlor from water and tea infusions with LOD of 0.03 μg/L. Another simple and cost‐effective analytical method using SDME with GC‐MS was developed to determine pretilachlor in water samples with LOD of 0.08 μg/L (Araujo et al, 2013). Similarly, Li et al (2013) reported pretilachlor detection using MSPE and GC‐ECD with LOD of 0.05 μg/L.…”
Section: Pretilachlor Estimation In Different Matricesmentioning
confidence: 99%
“…Sha‐Sha et al (2013) proposed magnetic solid‐phase extraction (MSPE) comprising graphene nanocomposite (G‐Fe 3 O 4 ) as the adsorbent, coupled with dispersive liquid–liquid microextraction (DLLME) using GC‐FID to detect five chloroacetanilide herbicides including pretilachlor from water and tea infusions with LOD of 0.03 μg/L. Another simple and cost‐effective analytical method using SDME with GC‐MS was developed to determine pretilachlor in water samples with LOD of 0.08 μg/L (Araujo et al, 2013). Similarly, Li et al (2013) reported pretilachlor detection using MSPE and GC‐ECD with LOD of 0.05 μg/L.…”
Section: Pretilachlor Estimation In Different Matricesmentioning
confidence: 99%
“…Headaches, dizziness, sweating, and other symptoms have been described because of fipronil poisoning in humans [ 7 ]. Currently, the most common techniques for detecting fipronil are gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), and gas chromatography (GC) [ 8 , 9 , 10 ]. However, these traditional methods have challenges, such as complex sample pretreatment, high cost, and dependence on trained staff.…”
Section: Introductionmentioning
confidence: 99%
“…5) Mepanipyrim residue is generally detected by using a chromatography technique, such as high-performance liquid chromatography (HPLC) with a diode array detector, liquid chromatography with tandem mass spectrometry, or gas chromatography with mass spectrometry. 6,7) The instruments used in these techniques are sensitive, accurate, and suitable for the multi-residue analysis of pesticides containing mepanipyrim. On the other hand, when detecting only mepanipyrim is the objective, enzyme-linked immunosorbent assays (ELISAs) are also useful methods.…”
Section: Introductionmentioning
confidence: 99%